DAMPAK PANDEMI COVID-19 TERHADAP PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KANTOR KECAMATAN SUNGAI TABUK - Irawanto Irawanto; Muhammad Fikri; Riky Welli Saputra (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
The purpose of this study was to determine the impact of the Covid-19 pandemic on population administration services at the Sungai Tabuk District Office.The research method used in this study is descriptive with a qualitative approach that describes the impact of Covid-19 on population administration services at the Sungai Tabuk District Office. Data collection techniques used are observation, interviews and documentation. The sources of information in this study were the Head of the Head of Government Section, the Staff of the Government Section, the Village Apparatus with as many as 3 (three) people, the Head of RT 1 person, and the community 3 people while the key informant was the Camat.The results of this research show that the impact caused by the Covid-19 pandemic on population administration services at the Sungai Tabuk District Office is reduced service time, the completion time of Population documents is getting slower, making ID cards cannot be done because the e-KTP recording device is damaged, transferred to the Office Population and Civil Registration of Banjar Regency with online services, the completion time of making an ID card takes quite a long time between 3 to 5 days or even more which is delivered by courier PT. J&T Express at a rate of Rp. 10,000 (Ten Thousand Rupiah).The online service that was implemented during the Covid-19 pandemic was difficult for some people because people did not understand technology and did not have a cellphone according to standards. The follow-up action taken by the Sungai Tabuk District Apparatus in direct service was to carry out health protocols, namely by providing a place for washing hands, wearing masks, maintaining a distance between service providers and recipients or fellow recipients and adding plastic shields to the service in front of the counter, to anticipate the spread of Covid -19.